Including topography and a 3D-elastic structure into a Finite-Element deformation model of Grímsvötn, Iceland - Sonja H. M. Greiner 1995- (2021)
Deformation models are an important tool to study subsurface processes at active volcanoes. Numerical deformation models can include complex irregular features like topography or crustal heterogeneity, avoiding the potential oversimplifications often necessary for analytical models. Elastic structures based on seismic velocities, provide the dynamic elastic modulus, but due to different strain amplitudes, the static modulus is relevant for deformation studies. However, since there is no commonly acknowledged relation between both types of elastic moduli, the dynamic one is often used in deformation models instead. A Finite Element deformation model was developed for the Icelandic subglacial volcano Grímsvötn, including real topography and a 3D elastic structure. The dynamic elastic moduli, which were derived from seismic velocity and density structures, were converted into static elastic moduli via a pressure-dependent relation. There is only one continuous GPS-station, GFUM, located on a nunatak on the caldera rim and the influence of its proximity to a steep cliff on deformation has not been studied previously. Based on GPS-observations from the 2011-eruption at Grímsvötn, depth and pressure change estimates for a shallow magma chamber were found testing different geometries. Combining the elastic structure with the topography enhances the influence of the topography, requiring a central magma chamber depth between 2-4 km below the caldera floor, and a co-eruptive pressure change of 5-50 MPa to fit the observed deformation. Independent of the geometry, the model requires larger source depths than previous analytical deformation studies suggested which shows the importance of considering crustal heterogeneity and static moduli in deformation models.